Computed Tomography–based Body Composition Analysis and Its Role in Lung Cancer Care. Issue 2 (March 2020) - Troschel, Amelie S.; Troschel, Fabian M.; Best, Till D.; Gaissert, Henning A.; Torriani, Martin; Muniappan, Ashok; Van Seventer, Emily E.; Nipp, Ryan D.; Roeland, Eric J.; Temel, Jennifer S.; Fintelmann, Florian J.
Abstract : Body composition analysis, also referred to as analytic morphomics, morphomics, or morphometry, describes the measurement of imaging biomarkers of body composition such as muscle and adipose tissue, most commonly on computed tomography (CT) images. A growing body of literature supports the use of such metrics derived from routinely acquired CT images for risk prediction in various patient populations, including those with lung cancer. Metrics include cross-sectional area and attenuation of skeletal muscle and subcutaneous, visceral, and intermuscular adipose tissue. The purpose of this review is to provide an overview of the concepts, definitions, assessment tools, segmentation techniques and associated pitfalls, interpretation of those measurements on chest and abdomen CT, and a discussion of reported outcomes associated with body composition metrics in patients with early-stage and advanced lung cancer. Abstract : Supplemental Digital Content is available in the text.